Cenozoic faulting response of eastern North China to subduction of the Pacific Plate: A case of study of the Luxi Block. (7th December 2017) - Li, Shaojun; Li, Sanzhong; Wang, Yongming; Li, Xiyao; Suo, Yanhui; Wang, Pengcheng; Wang, Qian; Zhang, Jian; Somerville, Ian
Abstract : The Cenozoic deformation and dynamic evolution of the eastern part of North China were significantly affected by the changing of the subduction direction and rate of the Pacific Plate. In this paper, we use the Luxi Block as a specific case study area, by examining the Cenozoic structural connection between the deep and shallow levels, and the related seismicities and their triggering mechanisms. We investigate the response of the Cenozoic tectonic activities in this area to the subduction of the Pacific Plate. The results show that the Cenozoic shallow fault pattern in the Luxi Block is mainly characterized by a domino‐style normal fault pattern constituted by a series of NW‐ to WNW‐trending normal faults. The focal mechanism and field observations suggest that these faults are sinistral strike‐slip type, and they dominate the formation and development of the Cenozoic basins jointly controlled by the NE‐trending faults. Geophysical data suggest that at a depth of 15–20 km beneath the Luxi Block, there is a gentle décollement zone and large‐scale low‐velocity tomographic anomalies. The domino‐style fault system in the shallow crust is incorporated into this décollement zone, manifesting as a decoupling between the shallow and deep structures, and a transition zone between the high‐ and low‐velocity anomaly zones controlling the development of two medium to strong NW‐trending earthquake zones. With respect to the dynamic mechanisms, the tectonic activities in eastern North China are closely related to the subduction of the Pacific Plate, which induced crustal thinning, mantle upwelling and small‐scale convections in the mantle wedge, and also caused the uplift of the Luxi Block.